Contemporary Views on Development of Excess Body Weight and Obesity in Children. Part I - M. V. Khodzhiyeva; V. A. Skvortsova; T. E. Borovik; L. S. Namazova-Baranova; T. V. Margieva; O. K. Netrebenko; T. V. Bushuyeva; N. G. Zvonkova; S. V. Nekrasova (Union of pediatricians of Russia, 2015)
Obesity is one of the most widespread chronic diseases around the world and may be considered a non-infectious epidemic. Virtually everywhere around the world the number of obese children doubles every three decades. Increase in the number of children with obesity and excess body weight is observed in Russia as well. Despite the statement that the main cause of obesity is energy expenditure/consumption imbalance, numerous data obtained in recent years indicate early factors of obesity forming, probably, during the period of intrauterine development and/or infancy and early childhood. The most active growth and maximum plasticity of metabolic processes is observed within 1,000 post-conceptual days, which cover the period of intrauterine development and the first 2 years of a child's life. The number and quality of nutrients received during that period considerably affect cell differentiation and organ development by means of gene expression, determine the nature of metabolism and affect health condition throughout the whole subsequent life. Given significance of the issue of excess body weight in children and adults, we analyzed the current situation, examined 652 younger Moscow schoolchildren and determined parameters of their physical development. We analyzed anamnestic data, profoundly examined children with excess body weight and obesity and formulated diets for them. This article presents the first stage of our work and a literature review.